International patterns and trends of childhood and adolescent cancer, 1978-2012 - Yawen Zhao; Peiyuan Sun; Jingyuan Xiao; Lan Jin; Ning Ma; Zhe Li; Guoshuang Feng; Huang Huang; Nicole C. Deziel; Xiaomei Ma; Xin Ni; Yawei Zhang (Journal of the National Cancer Center, 2022)
Background: This study aimed to provide a detailed analysis of the temporal trends of cancer incidence rates for individuals aged 0–19 years in selected regions globally from 1978 to 2012. Methods: Data were obtained from Volumes V-XI of Cancer Incidence in Five Continents (CI5), published by the International Agency for Research on Cancer. A total of 53 registries in 23 regions from the Americas, Asia, Europe, and Oceania that contained information on cancer incidence throughout 1978-2012 (35 years) were included in this study. Joinpoint regression was used for the analysis of trends. Results: Most regions showed increasing trends in overall childhood cancer among children (aged 0-14 years) and adolescents (aged 15-19 years). Nearly all regions showed rising trends in childhood and adolescent leukemia incidence rates, whereas the incidence of lymphoma among children generally decreased. Only France, Australia, and New Zealand showed decreasing trends for malignant central nervous system (CNS) tumors among adolescents. Kidney cancer and bone cancer incidence rates remained stable for most regions. The incidence of thyroid cancer among adolescents increased in most regions and that of testicular cancer decreased in approximately one-half of the regions studied. Conclusion: The international temporal trends of cancer incidents among children and adolescents are varied by region, cancer type, age group, and gender, and have changed over time.